Italy’s response to COVID-19 and the need for international cooperation - Staiano, María Francesca (2020)
The article proposes a first approximation to the international cooperation response against the novel coronavirus disease 2019 (COVID-19) pandemic. In particular, the paper aims to analyze the two fundamental strategies against the virus, with a focus on the Italian reaction and its consequences on European cooperation. The pandemic has accelerated some conflicts and claimed deeper international cooperation on health and the attempt to create a "community of shared health" for mankind.